Organization systems of school sports in China and France: A comparative study - Ruan, H.; Cai, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In China and France, physical education, which is an essential part of the whole school curriculum system, has given students health education, safety education mutual-aid education, responsibility and self-education. This paper attempts to analyze the school sports system, teaching objectives, contents and methods in China and France, in relation to historical, cultural, economic and social development. In addition, this paper seeks to reveal the similarities and differences that exist in the school physical education systems between China and France. Methods Study data was obtained through documentation analysis, logical analysis and comparative analysis, together with other research methods. Results / Discussion This study found that although the physical education systems in China and France have some overlapping teaching objectives and content, French physical education possesses the following significant features: Since 1880, physical education has been made compulsory in the primary and secondary school curriculum. Physical education has been given full attention by government and society, which can be seen from the following aspects; the primary and secondary education division, attached to the Ministry of Education, established a physical education section in charge of school physical education; the education minister is concurrently the Chairman of the Association of School Physical Education in France; all the people in charge of provincial and municipal education departments shall be the Chairmen of the regional School Physical Education Associations and each school is required to establish a sports association, Chaired by a president. Also, since 1959, physical education performance has been compulsory in college entrance examinations, accounting for 10% of the total scores. Weekly time dedicated to physical education varies: 3 hours in: primary school; 4 hours junior high school: 4 hours first grade, 3 hours second to fourth grade and 2 hours high school. PE teachers are required to have a high level of education, with personal specialties and multiple abilities. Physical education teachers must have a Bachelor`s Degree, followed by a two-year professional training course at university-level teacher training institutes along with teacher practice. Teachers must pass a national examination to obtain a certificate of qualification, with an admission rate of 6%. All these measures ensure the social status and teaching quality of the French school physical education system will undoubtedly serve as a useful reference for the reform of China's school physical education.